H44 The effects of a specific inpatient multidisciplinary rehabilitation program on postural and gait stability in huntington´s disease- a pilot study. (September 2018) - Brabcova, Libuse; Roth, Jan; Ulmanová, Olga; Rusz, Jan; Klempíř, Jiří; Horáček, Ondřej; Kolářová, Milena; Košková, Pavla; Rolková, Pavlína; Božková, Helena; Szabó, Lukáš; Inemanová, Monika; et al.
Abstract : Background: Postural and gait instability in Huntington's disease (HD) is an essential part of the motor symptomatology causing falls which contribute to morbidity and mortality. Rehabilitation (RHB) is considered beneficial in postural and gait stability treatment. Aims: We aimed to evaluate the short- and long-term effects of an inpatient multidisciplinary rehabilitation program on postural and gait stability in HD. Methods: A sample of 13 subjects with HD with no severe cognitive deficit or depression underwent a 3-week specific inpatient multidisciplinary rehabilitation program focused on postural and gait stability according to a steady protocol based on typical gait and stability problems in HD. The subjects were examined at the baseline, after the completion of the RHB, and 1 month and 3 months after the program. The testing included: gait stability examination (Dynamic Gait Index; DGI), posturography examination of postural stability- Limits of Stability, tested on a stable (PSS) and 20% unstable (PSU) platform and the total motor score evaluation by Unified Huntington's Disease Rating Scale (UHDRS). Results: There was a significant 3 months lasting improvement in PSS and a significant improvement in DGI immediately after the RHB. There was no significant improvement in PSU and UHDRS total motor score. Conclusions: Specific RHB methods may improve postural and gait instability in patients with early and mid-stage HD. The postural instability improvement measured by PSS persisted for at least 3 months. The gait stability improvement in DGI did not persist after 1 month. We found no improvement in PSU. This study offers a specific RHB protocol for stability training in HD.